40 on Justice: The Prophetic Voice on Social Reform. Book Review by Abdulkadir Salaudeen - Abdulkadir Salaudeen (Penerbit Hellow Pustaka, 2024)
Author : Omar Suleiman Book Title : 40 on Justice: The Prophetic Voice on Social Reform ISBN : 1847741436; 978-1847741431 Publisher : Kube Publishing Ltd Place of Publication : United Kingdom Page Number : 338 Price : 24.13 Year of Publication : 2021 Reviewer : Abdulkadir Salaudeen